Successful treatment of MRSA empyema in children: A case report - Pitaloka, Diah Ayu; Setyoningrum, Retno Asih (Edelweiss Applied Science and Technology, 2025)
The increasing prevalence of Methicillin-Resistant Staphylococcus aureus (MRSA) infection globally is largely attributed to community-acquired strains. Among pediatric patients, community-acquired MRSA has emerged as a significant cause of severe complications, including pneumonia with pleural effusion, empyema, necrotizing pneumonia, and abscess formation. Although staphylococcal pneumonia was previously uncommon in children, it is now associated with notable morbidity and mortality. This case report presents a 6-year-old and 11-month-old boy diagnosed with MRSA empyema. His treatment involved targeted antibiotic therapy guided by sputum culture results, pleural fluid drainage, and nutritional support. Given the limited available literature, this report highlights the diagnostic and therapeutic challenges in managing such cases and emphasizes the need for additional research to establish standardized treatment guidelines.